In vitro Delivery of HIV-1 Nef Antigen by Histidine-rich nona-arginine and Latarcin 1 peptide - Fatemeh Namazi; Azam Bolhassani; Seyed Mehdi Sadat; Shiva Irani (Pasteur Institute of Iran, 2019)
Introduction: The Nef accessory protein is an attractive antigenic candidate in the development of HIV-1 DNA- or protein-based vaccines. The most crucial disadvantage of DNA and protein-based vaccines is their low immunogenicity, which can be improved by cell-penetrating peptides (CPPs) as effective carrier molecules. Methods: In this study, the HIV-1 Nef protein was generated in the Escherichia coli expression system for in vitro delivery using a novel CPP, Latarcin 1 peptide, in a non-covalent manner. Also, the Histidine-rich nona-arginine peptide was utilized to transfer the HIV-1 Nef gene. The size, morphology, and zeta potential of the complexes were evaluated by scanning electron microscopy (SEM) and Zetasizer. The efficiency of cell transfection was studied using a fluorescence microscopy and flow cytometry for the DNA/CPP complexes and western blot analysis for the protein/CPP complexes. Results: The Nef protein generated in the BL21 strain migrated as a dominant band of ~30 kDa in SDS-PAGE. The SEM data confirmed the formation of stable complexes with a size below 200 nm. MTT assay demonstrated that the complexes did not represent any considerable cytotoxic effect compared to untreated HEK-293T cells. The results of fluorescence microscopy, flow cytometry, and western blotting revealed that the Nef DNA and protein constructs could be significantly transfected into HEK-293T cell line using these CPPs. Conclusion: These data suggest that the Histidine-rich nona-arginine peptide and Latarcin 1 peptide as CPPs can be considered as a promising approach in the development of the HIV-1 vaccine for gene or protein delivery.